2021
DOI: 10.47067/reads.v7i1.323
|View full text |Cite
|
Sign up to set email alerts
|

Employment Diversification Patterns in Pakistan: Empirical Assessment Revisited

Abstract: Employment diversification depicts a dynamic socio-economic process where domestic workers widen the range of employment sources. Whereas, the prospect is usually based on a mix of Part-time and Full-time employment. Employment decisions significantly derive from the economic incentives such as wage differentials and the growth rates in different sub-sectors of economic activity. Research at hand summarizes and analyses Employment Diversification Patterns in Pakistan and the motives behind the labor shift. Tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The non-agriculture activities now constates a large share of employment in much of the so-called rural areas (Nasir et al, 2021). Activities classified as 'non-farm' or 'nonagricultural' incomes, mainly services, constitute at least 60% of total rural incomes, taking in consideration the definition used for rural areas according to the (GoP, 2017) report.…”
Section: Rural Depiction In Pakistanmentioning
confidence: 99%
“…The non-agriculture activities now constates a large share of employment in much of the so-called rural areas (Nasir et al, 2021). Activities classified as 'non-farm' or 'nonagricultural' incomes, mainly services, constitute at least 60% of total rural incomes, taking in consideration the definition used for rural areas according to the (GoP, 2017) report.…”
Section: Rural Depiction In Pakistanmentioning
confidence: 99%
“…Its descriptive investigation signified opposite links of population growth with landholding, forest coverage, and HDI score. likewise, in Pakistan, Ahmadet al (2013), explored the impact of population growth on economic growth and originated that contributed of population growth has a positive and significant impact on economic expansion but is negatively exaggerated to unemployment in Pakistan (Shaheen at al., 2015;Nasir et al, 2021. More recently, Zhang (2015), investigated the association between population growth and economic development in Asian countries and finished that population growth affects economic development negatively in less developing countries such as China, India, and Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent decades showed that there has been a significant reduction in gender disparity in developed and developing countries; however, the remuneration of females is less than males for performing the same work. Employment in South Asia is extremely unbalanced insofar as females are concerned when we look at the educational indicators in the region (Nasir et al, 2021). The main emphasis of this research article paper is to access the contribution of education concerning female labor supply decisions, in addition, it further enhances the socio-economic wellbeing of the household and the entire economy (Klasen & Lamanna, 2009).…”
Section: Introductionmentioning
confidence: 99%